Cenário do diabetes mellitus tipo I na 9ª regional de saúde - Freitas, Wanya Maria Bulhões Viante Chaise de (2020)
Understanding the whole scenario that involves a particular disease, as well as epidemiological data on prevalence, are extremely important for Public Health actions, especially when it comes to chronic and non-contagious diseases such as Diabetes Mellitus (DM). This research aims to estimate the prevalence and present the scenario of type 1 Diabetes Mellitus, in the 9th Regional Health. It is a quantitative, sectional, observational, secondary and ecological research. Data collection took place by searching for information in the medical records of patients diagnosed with type 1 Diabetes Mellitus registered with ADIFI - Diabetic Association of Foz do Iguaçu and data from the Pharmaceutical Division of the 9th Regional Health - PR. 485 medical records were selected for the research. The mean age was 33.46 ± 17.62 years, with 50.81% of the records of females and 49.17% of males. The prevalence of DM1 in Foz do Iguaçu based on the collected sample was 14.6 cases / 10 thousand inhabitants and the 9th Regional was 12.4 cases / 10 thousand inhabitants, high values when compared to results of other studies on the prevalence of DM1 or the data registered in DATASUS. It was possible to observe that there is a flaw in the registration of cases in the available databases and there is no centralized control and monitoring of data regarding DM1. There is an emergency need for a satisfactory and sufficient information system to centralize such information in a practical way, as well as the elaboration of a protocol between managers and health professionals regarding the registration of cases, especially when there is the particularity of a region frontier where the flow of foreigners in search of health care is quite common and the effective control of these data that will serve as subsidies for diplomatic issues and the emergence of new agreements and exchanges of services in the area of health.